2021
DOI: 10.1101/2021.12.21.473723
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Striatal dopamine explains novelty-induced behavioral dynamics and individual variability in threat prediction

Abstract: Animals exhibit diverse behavioral responses, such as exploration and avoidance, to novel cues in the environment. However, it remains unclear how dopamine neuron-related novelty responses influence behavior. Here, we characterized dynamics of novelty exploration using multi-point tracking (DeepLabCut) and behavioral segmentation (MoSeq). Novelty elicits a characteristic sequence of behavior, starting with investigatory approach and culminating in object engagement or avoidance. Dopamine in the tail of striatu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
14
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 81 publications
2
14
0
Order By: Relevance
“…While previous work found differences in the intrinsic properties of mesolimbic dopamine (DA) neurons in susceptible and resilient individuals after stress was over; [3][4][5][6][7][8][9][10] the causal links between DA activity during stress, dynamic stress-evoked behavior, and individual differences in susceptibility and resilience are not known. Here, we record behavior and neural activity in DA projections to the nucleus accumbens (NAc, signals reward [11][12][13][14] ) and to the tail striatum (TS, signals threat [15][16][17][18] ) during a multiday chronic social defeat paradigm and discover behavioral and neural signatures of resilience. Using supervised and unsupervised behavioral quantification, we find that resilient and susceptible individuals employ different behavioral strategies during stress.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…While previous work found differences in the intrinsic properties of mesolimbic dopamine (DA) neurons in susceptible and resilient individuals after stress was over; [3][4][5][6][7][8][9][10] the causal links between DA activity during stress, dynamic stress-evoked behavior, and individual differences in susceptibility and resilience are not known. Here, we record behavior and neural activity in DA projections to the nucleus accumbens (NAc, signals reward [11][12][13][14] ) and to the tail striatum (TS, signals threat [15][16][17][18] ) during a multiday chronic social defeat paradigm and discover behavioral and neural signatures of resilience. Using supervised and unsupervised behavioral quantification, we find that resilient and susceptible individuals employ different behavioral strategies during stress.…”
mentioning
confidence: 99%
“…In addition, different DA projections in the striatum are known to perform distinct roles 38 . DA projections to the tail of the striatum (TS) are primarily from the lateral substantia nigra and are active in response to threatening [15][16][17][18] or alarming 39 stimuli. DA projections from the ventral tegmental area (VTA) to the nucleus accumbens (NAc) respond vigorously to rewards such as palatable food [11][12][13][14] and non-aggressive social investigation 40,14 .…”
mentioning
confidence: 99%
“…What is the relationship between stimulus intensity and threat avoidance? We previously proposed that TS dopamine signals physical salience of a stimulus as an initial estimate of threat level (Akiti et al, 2021), although the idea had not been tested experimentally. To address this, we next examined the relationship between physical salience of a threatening stimulus, TS dopamine activity, and avoidance behaviors (Figure 5A-D).…”
Section: Resultsmentioning
confidence: 99%
“…In the monster paradigm, we found that mice displayed dynamical threat management with avoidance, prediction, and overcoming of threat manifesting at different stages. We focused on TS, because we previously found that dopamine in TS is important for avoidance of a potential threat including a novel object (Akiti et al, 2021; Menegas et al, 2018). Interestingly, phasic dopamine responses in TS are modulated by various parameters that are known to affect physical salience of external stimuli (Menegas et al, 2018), suggesting that an initial estimate of the threat level is shaped by physical salience conveyed by phasic TS dopamine responses (Akiti et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation